DONALD TRUMP AND BARRACK OBAMA’S INAUGURAL ADDRESS: STYLISTIC ANALYSIS - Agung Suhadi; Kiagus Baluqiah (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
The two Presidents of U.S., Barack Obama (former) and Donald Trump displayed outstanding rhetorical craftmanship to drive the power of persuasion that gave them a victory. This study explores by taking up the 2009 Inaugural Speech of President Barack Obama and Donald Trump in 2016 as the target of stylistic analysis. To achieve this objective, this study analyzes the oral communication by corncerning on the content of speeches and how it was carried out as well. In order to identify the “what” and “how” questions will be formulated through research questions; what promise and requests are made, how does intertextuality strengthen the speech, what are the lexical features and what are the reference of politically loaded pronouns in the speech. The result of this study showed that Obama’s inaugral speech style is more communicative, evocative and its message conveyed orderly. While, Trump’s style is more conversationally, but it was able to awaken audiences through huge topics are delivered, for instance American first, transfering power, nation etc.